The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/0471140856.tx0709s49
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Peroxiredoxins in Oxidant Defense and Redox Regulation

Abstract: Peroxiredoxins are important hydroperoxide detoxification enzymes, yet have only come to the fore in recent years relative to the other major players in peroxide detoxification, heme-containing catalases and peroxidases, and glutathione peroxidases. These cysteine-dependent peroxidases exhibit high reactivity with hydrogen peroxide, organic hydroperoxides and peroxynitrite and play major roles not only in peroxide defense, but also in regulating peroxide-mediated cell signaling. This overview focuses on import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 95 publications
0
67
0
1
Order By: Relevance
“…1). These proteins belong to the Prx5 subfamily, which is classified based on the conservation of sequences proximal to the active site (8). Prx3 contains N-terminal cysteine (Cys-48) within the PXXXTXXC motif at the active site and second cysteine (Cys-73), which are highly conserved in members of the Prx5 subfamily ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). These proteins belong to the Prx5 subfamily, which is classified based on the conservation of sequences proximal to the active site (8). Prx3 contains N-terminal cysteine (Cys-48) within the PXXXTXXC motif at the active site and second cysteine (Cys-73), which are highly conserved in members of the Prx5 subfamily ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of bacterial defense against oxidative stress include highly specific and effective antioxidant enzymes (4 -7). Among them, peroxiredoxins (Prxs) are a ubiquitous family of cysteinebased peroxidases widely distributed across all kingdoms of life and catalyze the reduction of peroxides, such as H 2 O 2 , organic hydroperoxide, and ONOO Ϫ (6,8). Based on catalytic mechanisms, Prxs are divided into three classes referred to as typical 2-Cys, atypical 2-Cys, and 1-Cys Prxs (9).…”
mentioning
confidence: 99%
“…The antioxidative activity of peroxiredoxin is the first to be studied and is known as the compound's most general biological function. However, recent research has shown that peroxiredoxins also function in signal transduction (Jarvis et al 2012;Poole et al 2011;Wood et al 2003a) and the regulation of phospholipid metabolism (Chen et al 2000;Manevich and Fisher 2005;Manevich et al 2013;Nevalainen 2010). However, the inactivation of peroxiredoxins at high H 2 O 2 levels can turn off peroxide defenses and preserve the pool of reduced thioredoxin; thus, peroxiredoxin can be used to repair proteins vital to survival (Karplus and Poole 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, Prxs share a common fold and active site as well as a catalytic cycle that uses a conserved Cys residue, called Cys47 (Hall et al 2009;Poole et al 2011;Wood et al 2003b). In the typical catalytic mechanism for Prxs, sulfenic acid is captured by the active site, and H 2 O 2 is reduced to H 2 O while the active site cysteine is oxidized to sulfenic acid (Karplus and Poole 2012;Poole et al 2011). Among the types of peroxiredoxins, 1-Cys Prx, a homodimer with a subunit molecular weight of 25 kDa, has been studied the least.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxiredoxins are a relatively recently described family of nonseleno peroxidases that generally utilize thioredoxin as a physiological reductant (65). They have been classified as 2-cys or 1-cys proteins, depending on the number of cysteine residues that are involved in catalysis.…”
Section: Peroxiredoxinsmentioning
confidence: 99%